A Randomized Controlled Trial Assessing Growth of Infants Fed a 100% Whey Extensively Hydrolyzed Formula Compared With a Casein-Based Extensively Hydrolyzed Formula - David Fields PhD; Laura Czerkies MS, RD; Shumei Sun PhD; Heidi Storm MS, RD; José Saavedra MD; Ricardo Sorensen MD (SAGE Publishing, 2016)
This study compared the growth of healthy infants fed a hypoallergenic 100% whey-based extensively hydrolyzed formula (EHF) with Bifidobacterium lactis (test) with that of infants fed an extensively hydrolyzed casein formula (control). Formula-fed infants (14 ± 3 days) were randomized to test or control groups until 112 days of age. Anthropometrics were assessed at 14, 28, 56, 84, and 112 days, and daily records were kept for 2 days prior to study visits. Serum albumin and plasma amino acids at 84 days were assessed in a subset. A total of 282 infants were randomized (124 test, 158 control). Significantly more infants dropped out of the control (56%) as compared with the test (41%) group. Mean daily weight gain was significantly higher in the test group compared with the control group (27.95 ± 5.91 vs 25.93 ± 6.12 g/d; P = .027) with the test group reporting significantly fewer stools (2.2 vs 3.6 stools/d; P < .0001). The control group reported significantly more days with >3 loose stools/d and a higher incidence of vomiting as compared with the test group. There were no differences in gas, mood, sleep, or serum albumin. Plasma arginine and valine were significantly lower in the test group, whereas leucine and lysine were higher; all values were within normal limits. Significantly more adverse events attributed to the study formula were reported in the control group. The 100% whey-based hypoallergenic EHF containing Bifidobacterium lactis and medium chain triglycerides supported growth of healthy infants. Future studies on the application of this formula in clinically indicated populations are warranted.